A System for Incubations at High Gas Partial Pressure - Sauer, Patrick; Glombitza, Clemens; Kallmeyer, Jens (Frontiers in Microbiology, 2012)
High-pressure is a key feature of deep subsurface environments. High partial pressure of dissolved gasses plays an important role in microbial metabolism, because thermodynamic feasibility of many reactions depends on the concentration of reactants. For gases, this is controlled by their partial pressure, which can exceed one MPa at in-situ conditions. Therefore, high hydrostatic pressure alone is not sufficient to recreate true deep subsurface in-situ conditions, but the partial pressure of dissolved gasses has to be controlled as well. We developed an incubation system that allows for incubations at hydrostatic pressure up to 60 MPa, temperatures up to 120° C and at high gas partial pressure. The composition and partial pressure of gasses can be manipulated during the experiment. The system is mainly made from off-the-shelf components with only very few custom-made parts. A flexible and inert PVDF incubator sleeve, which is almost impermeable for gases, holds the sample and separates it from the pressure fluid. The flexibility of the incubator sleeve allows for sub-sampling of the medium without loss of pressure. Experiments can be run in both static and flow through mode. The incubation system described here is usable for versatile purposes, not only the incubation of microorganisms and determination of growth rates, but also for chemical degradation or extraction experiments under high gas saturation, e.g. fluid-gas-rock-interactions in relation to carbon dioxide sequestration. As an application of the system we extracted organic acids from sub-bituminous coal using H2O as well as a H2O-CO2 mixture at elevated temperature (90°C) and pressure (5 MPa). Subsamples were taken during the incubation and analysed by ion chromatography. Furthermore we demonstrated the applicability of the system for studies of microbial activity, using samples from the Isis mud volcano. We could detect an increase in sulphate reduction rate upon the addition of methane to the sample.